Adverse Impacts of Temporomandibular Disorders Symptoms and Tooth Loss on Psychological States and Oral Health-Related Quality of Life During the COVID-19 Pandemic Lockdown - Weng, Siwei; Hou, Sicong; Jiao, Xiuping; Sun, Yun (Frontiers in Public Health, 2022)
Background: Emotion and quality of life may have been impacted by the coronavirus disease 2019 (COVD-19) crisis, especially in the lockdown. The impact of temporomandibular disorders (TMD) symptoms and tooth loss on mental status and Oral Health-Related Quality of Life (OHRQoL) are not completely clear under the stressful event. Objectives: We aimed to investigate whether TMD and tooth loss were the impaired risks of psychological states and OHRQoL in COVID-19 lockdown, and attempt to explore other potential risk factors. Methods: This cross-sectional study surveyed residents via an online self-reported questionnaire, when Yangzhou was in lockdown. Demographic data, clinical information, the level of anxiety, depression and OHRQoL were collected and analyzed. Results: Painful TMD symptoms and tooth loss are the risks of more severe anxiety and depression. TMD symptoms and tooth loss worsened OHRQoL. Lower education degree (OR: 6.31, P =0.019), TMD-related pain symptoms (OR: 10.62, P = 0.005), tooth loss (OR: 3.12, P = 0.035), sleep disorders(OR: 2.92, P = 0.049) and relatively close contacts (OR:3.95, P = 0.020) were verified as risk factors for increased level of anxiety. With respect to depression, low socio-economic status (OR: 6.22, P = 0.021), TMD-related pain (OR: 7.35, P = 0.012), tooth loss (OR: 4.48, P = 0.009), sleep disorders(OR: 5.13, P = 0.007) and relatively close contacts (OR: 12.94, P = 0.001) were identified as independent factors for developing depression. Additionally, drinking (B: -2.584, P = 0.013) and never going to the dental clinic (B: -3.675, P = 0.024) were relevant to better OHRQoL, while TMD without pain(B: 2.797, P = 0.008), TMD-related pain (B: 12.079, P < 0.001), tooth loss(B: 2.546, P = 0.006), sleep disorders(B: 2.598, P = 0.003) were independent factors for impaired OHRQoL. Conclusions: Painful TMD symptoms, tooth loss and sleep disorders were the impaired risks of psychological states. TMD symptoms and tooth loss damaged OHRQoL when the city was in lockdown. Therefore, individualized psychological counseling is supposed to maintain control of mental health and OHRQoL under the stressful event.